Synthesis Of Zinc Selenide Quantum Dots By Successive Ionic Layer Adsorption And Reaction (SILAR) Method For Quantum Dot Sensitized Solar Cells (QDSSC) - Chang, Wan Ling (Universiti Sains Malaysia, 2018)
Quantum dot sensitized solar cells (QDSSCs) have been intensively concerned in the past decades. Zinc selenide (ZnSe) is an alternative material to replace toxic cadmium-based quantum dots (QDs). In this research, ZnSe QDs were deposited on TiO2 electrode as TiO2 photoanode using successive ionic layer adsorption and reaction (SILAR) method for QDSSCs. TiO2 electrode was formed with the deposition of TiO2 mesoporous film on fluorine doped tin oxide (FTO) glass after the sintering in furnace at 370 °C for 10 minutes, the temperature was increased to 450 °C and held for 30 minutes. Solar cells were prepared by sandwiching the TiO2 photoanode and Cu2S counter electrode with polysulfide electrolyte in the between. Effect of fluoride treatment on TiO2 mesoporous film prior to deposition of ZnSe QDs, number of SILAR cycles (5, 10, 15, 20 and 25), molar concentration of zinc acetate dihydrate solution (0.03 M, 0.05 M, 0.1 M, 0.3 M and 0.5 M), and the effect of ZnS blocking layer coating after ZnSe layer was studied. The samples were prepared and characterized with X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), energy dispersive X-ray spectroscopy (EDX), high resolution transmission electron microscope (HRTEM), atomic force microscope (AFM), UV-visible (UV-vis) spectroscopy, and current density-voltage (J-V) measurement. ZnS blocking layer was found that did not contribute in improving the efficiency of QDSSCs due to its wide band gap of 3.10 eV. Generally, as number of SILAR cycles and molar concentration of precursor solution increased, the efficiency increased due to more and bigger ZnSe nuclei were formed in the TiO2 mesoporous film. However, pore-blocking on the TiO2 mesoporous structure may occur due to overloading of QDs. Sample with 20 SILAR cycles shows the highest efficiency of 0.6988 % while deposition using 0.1 M zinc acetate dihydrate solution shows efficiency of 0.5956 %. The sample with fluoride treatment on TiO2 mesoporous film also shows the higher efficiency of 0.4485 % than without fluoride treatment of 0.0679 %. In this research, the results can be concluded to suggest to carry out fluoride treatment on TiO2 mesoporous film prior deposition of 20 SILAR cycles of ZnSe QDs with 0.1 M of zinc acetate dihydrate solution.